A case of critical ischemia of the lower limbs: critical elements and possible medico-legal implications - Basile, Giuseppe; Petrucci, Quirino Alessandro; Ghezzi, Marcello; Amadei, Federico; Bianco Prevot, Luca; Accetta, Riccardo; Fozzato, Stefania (Acta Biomedica Atenei Parmensis, 2022)
Peripheral arterial disease (PAD) is an atherosclerotic process that causes stenosis and occlusion of non-cerebral and non-coronary arteries. Critical ischemia of the lower limbs is the most advanced and severe state of arterial disease. The purpose of this work is to underline the importance of a timely diagnostic-therapeutic framework in case of critical ischemia of the lower limbs, through a precise, coordinated, and multidisciplinary teamwork. A significant example is represented by the presentation of a clinical case that came to our observation following a request for compensation and which required an adequate evaluation in the medical-legal field.This work will make possible to clarify any profiles of medical professional responsibility, with specific reference to the predictability and preventability of the unfavorable events that have occurred, and which have led to a progressive worsening of the patient's clinical condition, which then resulted in the amputation of the lower limb, associated to organic deterioration and progressive complete permanent disability. In these cases, the collection of semeiological data must be careful, meticulous, and completed by suitable instrumental investigations. These data, with the exhaustive compilation of the medical record, play a decisive role even in the presence of adverse events and/or infrequent complications, in order to demonstrate from a medico-legal point of view that despite the implementation of all precautions codified by the specialized discipline, the adverse event, however foreseeable, is not always concretely preventable and therefore avoidable, being included in the non-negligent "complication" and not necessarily attributable to professional responsibility.